Enhanced osteogenic activity of titania-modified zirconia implant by ultraviolet irradiation - Tang, Shuang; Wang, Yan; Zong, Zhenyu; Ding, Ning; Zhang, Zutai (Frontiers in Bioengineering and Biotechnology, 2022)
Zirconia is a superior implant material owing to its high mechanical strength, durable corrosion resistance, superior aesthetic effect and excellent biocompatibility. However, the bioactivity of zirconia surfaces remains a great challenge for implant osseointegration. A titania (TiO2) coating was innovatively synthesized on the surface of zirconia by infiltration in a suspension of zirconium oxychloride and titania for dense sintering. Subsequently, the coating was subjected to ultraviolet (UV) light to enhance the biological inertness of zirconia. Scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) and contact angle analysis were conducted to confirm the surface characteristics. Afterwards, in vitro assessments of cell adhesion, proliferation and osteogenic differentiation of MC3T3-E1 cells were performed. Zirconia samples were implanted into rat femurs to assess biocompatibility and host tissue response in vivo. Micro-CT evaluation and histological testing were conducted. After UV irradiation, the content of hydroxyl groups and hydrophilicity of TiO2-modified zirconia were significantly increased. The results of in vitro experiments showed that TiO2-modified zirconia subjected to UV light could promote cell proliferation and spreading, enhance ALP activity and the degree of mineralization, and upregulate osteogenesis-related genes. Furthermore, in vivo assessments confirmed that UV-irradiated TiO2-modified zirconia implants maximized the promotion of osseointegration. TiO2-modified zirconia after UV treatment will have broad clinical application prospects in improving the osseointegration of zirconia implants.